2014
DOI: 10.1007/s00441-014-1940-7
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between sirtuin 1 and transcription factors p53 and NF-κB (p50/p65) in the control of ovarian cell apoptosis and proliferation

Abstract: The roles of the mTOR system enzyme sirtuin 1 (SIRT1), the transcription factor p53 and the nuclear factor kappaB (NF-κB) and their interrelationships in the control of ovarian function have not been well studied. We examine, in vitro, the involvement of SIRT1, p53 and the p65 and p50 subunits of NFκB and their interrelationships in the control of the apoptosis and proliferation of porcine ovarian granulosa cells. Monolayers of primary granulosa cells were transfected with cDNA constructs encoding SIRT1, p53, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 30 publications
2
25
0
4
Order By: Relevance
“…In the present study, no effect of either PF 046 or WYE 687 on porcine granulosa cell apoptosis was observed as well. Moreover, transfection with SIRT1 gene construct did not alter the apoptosis of porcine granulosa cells in our previous experiment (Sirotkin et al, 2014). However, the inhibition of mTORC1/2 by NVP-BEZ235 and DS-7423 increased the apoptosis of human ovarian cancer cells (Santiskulvong et al, 2011;Kashiyama et al, 2014), indicating the possible involvement of mTOR in the control of at least human ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In the present study, no effect of either PF 046 or WYE 687 on porcine granulosa cell apoptosis was observed as well. Moreover, transfection with SIRT1 gene construct did not alter the apoptosis of porcine granulosa cells in our previous experiment (Sirotkin et al, 2014). However, the inhibition of mTORC1/2 by NVP-BEZ235 and DS-7423 increased the apoptosis of human ovarian cancer cells (Santiskulvong et al, 2011;Kashiyama et al, 2014), indicating the possible involvement of mTOR in the control of at least human ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 64%
“…The involvement of the mTOR system in both the up-and down-regulation of ovarian cell proliferation is supported by previous experiments that manipulated SIRT1, a physiological inhibitor of the mTOR system. The transfection of porcine granulosa cells with an SIRT1 gene construct was able to either stimulate or inhibit the cell proliferation of these cells (Pavlova et al, 2013;Sirotkin et al, 2014). The SIRT1 inhibition by sirtinol resulted in the reduced proliferation of a human ovarian granulosa-like tumour cell line (Benayoun et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data reported that the SIRT1/NF-kB system mediates FSH activity on progesterone and IGF-1 release (34). Thus GC fate may depend on the balance between inhibitory and stimulatory influences on SIRT1 (35). Moreover, stimulation of SIRT1 by resveratrol provides evidence for direct involvement of SIRT1 in the upregulation of ovarian hormone secretion (34).…”
Section: Sirtuins Expression and Functions In The Mammalian Folliclementioning
confidence: 99%
“…These observations suggest that SIRT1 can promote ovarian functions via activation of the GnRH–gonadotropin–ovarian gonadotropin receptor axis, although direct action of SIRT1 on the ovarian cells is also evident. Transfection with a SIRT1 gene construct stimulated proliferation (but not apoptosis), progesterone, testosterone, and IGF-1 release by cultured porcine granulosa cells [23,24] and developmental capacity of mouse and human oocytes [25]. Either FSH or OT additions increased the SIRT1 accumulation in cultured porcine ovarian granulosa cells, while IGF-I addition decreased it.…”
Section: The Use Of Sirts To Study Control and Treat Ovarian Funmentioning
confidence: 99%